2005
DOI: 10.1097/01.bsd.0000128694.21405.80
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Bone in Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: Pseudarthrosis rate of 2.7% and loss of correction of 5.9% are comparable with or better than those in previous reports using autogenous bone graft and either segmental or nonsegmental instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
3
22
0
2
Order By: Relevance
“…16,17,23 Despite this, our data support the study by Sponseller and colleagues, 4 identifying the use of allograft as a significant risk factor within the entire cohort and when adjusted for effect modifiers (e.g., nonidiopathic or neuromuscular diagnoses). The reasons for this finding are not clear, but may include the overwhelming of host defenses by the presence of a large amount of devitalized bone in patients who were already relatively immunocompromised.…”
supporting
confidence: 36%
See 1 more Smart Citation
“…16,17,23 Despite this, our data support the study by Sponseller and colleagues, 4 identifying the use of allograft as a significant risk factor within the entire cohort and when adjusted for effect modifiers (e.g., nonidiopathic or neuromuscular diagnoses). The reasons for this finding are not clear, but may include the overwhelming of host defenses by the presence of a large amount of devitalized bone in patients who were already relatively immunocompromised.…”
supporting
confidence: 36%
“…15 The use of allograft has also been suggested to increase the risk of infection, but this conclusion remains controversial. 4,16,17 The diagnosis of infection is difficult to establish but is suggested by pain, 18 the presence of a sinus tract, persistent or late postoperative wound drainage, erythema, wound dehiscence, positive culture from a wound aspirate, instrumentation failure/pseudoarthrosis and pathologic confirmation of the presence of inflammatory cells and/or the offending organism(s). 1,3,5,6,19 Staphylococcus aureus 1,12,15 and S. epidermidis 2,5,20 have been reported to be the most common causative organisms.…”
mentioning
confidence: 99%
“…It had the added advantage of avoiding donor site morbidity and increased blood loss (Banwart et al 1995;Cockin 1971;Kreibich et al 1994;Summers and Einstein 1989). This is in support of other studies that have observed that cancellous allograft is effective in achieving spinal fusion (Knapp et al 2005;Lobo Gajiwala et al 2003;Marczynski et al 1999).…”
Section: Discussionsupporting
confidence: 68%
“…With the minimum follow up of 3 years, no loss of correction or pseudarthrosis was identified. Studies have also shown allograft bone to be as effective as autograft bone in posterior spinal fusion [5,10]. In our study, we found the combination of autograft and allograft bone provided good results in the treatment of AIS, i.e., no failure of fusion were seen on radiographs, percent correction was well maintained, and no patients complained of back pain.…”
Section: Discussionsupporting
confidence: 66%
“…The high morbidity of iliac crest bone graft harvesting has limited its application. Allograft bone has the advantages of adequate supply and variety of type, and reports indicate that allograft bone is a suitable alternative to autogenous bone grafting for AIS corrective surgical procedures [4,5]. …”
Section: Introductionmentioning
confidence: 99%